UV- C Light Mobile Robotics System - Gowri, R. Punitha; Kiruba, K.; Kiran, G.R.; Dhanush, M.U. (Journal of Electronics and Informatics, 2024)
Because diseases are spreading, cleaning enclosed places has become a critical concern. Various methods, including chemical-based solutions in liquid and gas forms, are commonly used for pathogen eradication. However, the environmental damage caused by these methods compounds existing challenges facing humanity. Additionally, UVC light, a promising alternative for disinfection, poses risks to human skin and eyes, necessitating precautions to prevent exposure. Moreover, the effectiveness of UVC disinfection is limited to directly exposed surfaces, rendering it challenging to utilize in occupied spaces where thorough disinfection is crucial. Furthermore, UVC light is less effective on porous surfaces like wood and fabric, further limiting its efficacy. The suggested solution incorporates UVC disinfection technology together with cleaning and drying features to overcome these issues. The objective is to improve the cleaning efficacy and efficiency of enclosed spaces by merging these elements. Both surface disinfection and impurity elimination are the main goals of the mopping and drying functions, which guarantee thorough cleaning. By using clever navigation algorithms to make sure all surfaces have direct exposure to UV-C lamps, the technology also overcomes the shortcomings of existing UVC disinfection. As porous surfaces react less well to UVC disinfection alone, the combination of cleaning and drying activities makes treatment possible. The proposed study provides a brief review of the methods used in sanitation with and without UV rays and the specific range of UV rays utilized in sanitation. It suggests an innovative UV-C sanitation robotic system that overcomes the shortcomings of existing UV-C disinfection systems.
Keywords: Ultraviolet-C; UV-C radiation; Bluetooth wireless interface; sanitizing system; UVC disinfection technology; cleaning and drying features; cleaning efficacy; UV-C lamps